2004
DOI: 10.1097/00005176-200410000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Inflammatory Bowel Disease in Children and Adolescents: A Cross-Sectional Study

Abstract: These findings support the recommendation that adolescents with IBD in outpatient medical care settings, particularly older adolescents and those on steroids, should be screened for depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
161
4
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(181 citation statements)
references
References 57 publications
11
161
4
3
Order By: Relevance
“…This finding suggests that the complex chronically ill children at freestanding children' s hospitals have a relatively high burden of mental health comorbidities, which is consistent with studies in chronically ill pediatric outpatients. [25][26][27][28][29] We also found that the most common comorbid mental health diagnoses differed between hospitals nationally and free-standing hospitals.…”
Section: Discussionmentioning
confidence: 57%
“…This finding suggests that the complex chronically ill children at freestanding children' s hospitals have a relatively high burden of mental health comorbidities, which is consistent with studies in chronically ill pediatric outpatients. [25][26][27][28][29] We also found that the most common comorbid mental health diagnoses differed between hospitals nationally and free-standing hospitals.…”
Section: Discussionmentioning
confidence: 57%
“…Both patients and staff reported acceptance of screening on qualitative surveys. Elevated CDI scores ($16) were found in 8% of the sample; moderate scores (10)(11)(12)(13)(14)(15) in 12% of the sample. Low risk scores were found in 80% of the sample.…”
Section: Resultsmentioning
confidence: 91%
“…Up to 9.5% of the general population of adolescents are depressed, [8][9][10] and the rate is 2 to 3 times higher for adolescents with type 1 diabetes and other chronic health conditions. [11][12][13][14][15][16] When present, depression in adolescents with type 1 diabetes is associated with less frequent blood glucose monitoring (BGM), 17 higher HbA1c values, [18][19][20][21] and increased rates of diabetes-related hospitalizations. 22,23 All of these negative health outcomes are associated with higher risk of longterm complications from diabetes and consequent increase in medical care costs.…”
Section: Resultsmentioning
confidence: 99%
“…It is well established that mental health disorders, particularly depression and anxiety, are prevalent comorbid conditions in adult as well as young patients with IBD ( 8,25,32,33 ). However, data on the incidences of anxiety disorders and depression specifi cally for young patients with CD are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Szigethy et al ( 25 ) conducted a study of 102 patients aged 11 -17 years with IBD, and estimated that 24.5 % had clinically meaningful symptoms of depression. Further, patients with active IBD had signifi cantly more symptoms of depression than did patients who were in remission ( 25 ). Epidemiologic studies have indicated that an early onset of mental health disorders (e.g., anxiety and depression disorders) predicts poor long-term outcomes and chronic, recurrent mental health disorders in young adulthood and adulthood ( 26,27 ).…”
Section: Increased Risks Of Developing Anxiety and Depression In Younmentioning
confidence: 99%